Key decision-making criteria for dormancy-breaking and ability to form seed banks of Cerrado native tree species - Maria Luciana Zequim Colado; Letícia Koutchin Reis; Angélica Guerra; Bruno Henrique dos Santos Ferreira; Diego Rezende Fonseca; Amanda Timóteo; Evânia Xavier Gondim; Natalia Guerin; Letícia Couto Garcia (Acta Botânica Brasílica, 2021)
ABSTRACT Ecological restoration by direct seeding in the Cerrado biome still lacks information about native species germination, the need for dormancy overcoming and seed bank formation. This study aims to verify the effects of dormancy overcoming on germination of four tree species and the ability of 12 tree species to form seed banks for restoration use. Our results showed wide variation of species’ germination rates. Overcoming dormancy enhanced germination for Dimorphandra mollis, Hymenaea stigonocarpa, and Peltophorum dubium and decreased it for Copaifera langsdorffii, but was only cost-effective for H. stigonocarpa. Regarding the ability to form seed banks, only H. stigonocarpa and Cecropia pachystachya germinated and live seedlings of Terminalia corrugata were found after being buried for six months, thus forming a transient seed bank. Despite the fact that overcoming dormancy may optimize germination after direct seeding, maintaining dormancy mechanisms of species that can form seed banks could be essential for species establishment over time in restoration areas. Hence, our key decision criteria based on seed costs and seed and labor availability would be useful for the seeding actions of restoration practitioners.